Cytomegalovirus Infection in Children: Treatment Approaches in Different Course of Infection - Ye.I. Yulish (Zaslavsky O.Yu., 2015)
Diseases caused by cytomegalovirus infection largely determine the health status of children that is due to the spread of infection and often due to its severity. The paper presents approaches to rational and effective therapy in different course of infection.